A medico-legal approach to developing a structured decision-making process for patients refusing blood transfusions - Tattoli, Lucia; Santovito, Davide (Frontiers in Public Health, 2025)
IntroductionThe healthcare providers should respect patients’ autonomy in making treatment decisions, which affect their health and wellbeing. Refusing life-saving treatments like blood transfusions raises ethical and legal concerns that should be discussed in informed consent. The dilemma is between respecting patient’s autonomy and beneficence principle, the physician’s duty of care. This article explores the communication and information process to provide to adult patients who refuse blood transfusions or related blood products, focusing on legal frameworks, clinical practices, and medico-legal risk management.MethodsThe authors conducted a retrospective analysis of medico-legal consultations on patients ‘refusal of blood and blood components transfusions in the Hospital “Città della Salute e della Scienza” of Turin (Italy) from 2017 to 2021. The Authors divided the consultation process into seven phases and 27 sub-phases which were analyzed through the PROSA risk assessment software. The strengths, weaknesses, opportunities, and threats (SWOT) analysis was used to evaluate the efficacy and potential of this structured protocol of consultation in clinical applications.ResultsBased on 16 medico-legal consultations, high-risk sub-phases include medical record analysis, care pathway selection shared by the equipe; alternative therapy identification; communication regarding the transfusion and the Patient Blood Management process; communication regarding the not feasibility without transfusion. SWOT analysis showed that the informed consent process indicated advantages in 74% of aspects versus disadvantages in 26%.DiscussionHealthcare professionals should follow predictable, effective, efficient, transparent, and traceable guidelines when dealing with patients who refuse blood transfusions. A structured communication process, as a part of the informed consent, offers a replicable framework that can be adapted to other clinical contexts where high-stakes decision-making intersects with patient rights, supporting a culture of safety, transparency, and continuous improvement in healthcare delivery, while also helping to mitigate medico-legal risk and potential legal action.